PERTUMBUHAN DAN PATOGENISITAS BEBERAPA ISOLAT MUTAN Metarhizium anisopliae TERHADAP HAMA PENGHISAP POLONG (Riptortus linearis) - Puji Astuti; Yuyun Fitriana; Lestari Wibowo; FX Susilo (Jurnal Agrotek Tropika, 2020)
Growth and pathogenicity of Metarhizium anisopliae mutant isolates on pod sucking bug (Riptortus linearis). This study aimed to determine the growth ability of Metarhizium anisopliae mutant (colony diameter, spore density, and viability) and the ability of M. anisopliae to cause mortality in pod sucking bug(Riptortus linearis). The study conducted at the Laboratory of Agricultural Biotechnology, Faculty of Agriculture, University of Lampung. The study began in December 2016 - April 2017. M. anisopliae used in this study were isolate B wildtype (MYFT B), mutant M. anisopliae 1 (MYFT 1), mutant M. anisopliae 42 (MYFT 42), and M. mutant anisopliae 51 (MYFT 51). The results of this study indicated that the Myft B isolate (wildtype) had the widest diameter (5.50 cm) with the highest spore density in the MYFT 42 mutant isolate (7.4000 x 108 spores / ml) and the highest viability in theMYFT 51 mutant isolate (96.750% ). MYFT 51 and MYFT 42 mutant isolates were able to cause 100 % mortality of R. linearis and significantly higher compared to the MYFT 1 mutant isolates and wildtype MYFT B.